Total phenolic content and antioxidant activity of selected fruits at different maturity stages - Pheen, Chee Leong (2014)
The total phenolic content and antioxidant activity for local fruits (Salacca zalacca, Mangifera indica L. Chok Anan and Baccaurea motleyana Hook.f) at three different were studied by using Folin-Ciocalteu method and DPPH radical scavenging assay respectively. Total phenolic content ranged from 65.10mg GAE/100g to 381.00mg GAE/100g, whereas the antioxidant activity ranged from 2.94% - 84.55%. The highest phenolic content and antioxidant activity were found in the young stage of Salacca zalacca fruit. It contains the lowest inhibitory concentration (IC₅₀) value (0.56mg/m1). On the other hand, IC₅₀ value for Baccaurea motleyana Hook.f with different maturity stages was unable to be calculated due to its low antioxidant capacity. There was a significant positive linear correlation between the total phenolic content and antioxidant activities on the fruit studied, However. total phenolic content and antioxidant activity in the three fruits varies irregularly when maturity progressed. This research suggests that studied fruits at young maturity stage are a better source of phenolic compounds and antioxidants.